2018
DOI: 10.1590/0100-29452018302
|View full text |Cite
|
Sign up to set email alerts
|

Advances in pineapple plant propagation

Abstract: Pineapple is one of the most important fruits, with large production in tropical and subtropical regions and great appreciation by consumers all over the world. The pineapple plant has many specific morphological, anatomical and physiological characteristics that determine crucial aspects of pineapple crop management, such as flower induction, water use and vegetative methods of propagation. The use of sexual reproduction of pineapple is restricted to breeding purposes carried out by research institutes lookin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
(35 reference statements)
0
24
0
3
Order By: Relevance
“…The growth period for these plantlet can vary (REINHARDT; CUNHA, 1999;GOMES et al, 2003) for slip-type plantlet, from one to six months, and for shoot-type plantlet, from two to 12 months after the harvest of fruits (REINHARDT; CUNHA, 1999). In addition, it has been elucidated that conventional plantlet are more vigorous and they should have at least 30 cm to be considered suitable for planting (REINHARDT et al, 2018). Additionally, it was observed that the matrices whose shoots were 10 cm in size produced, simultaneously, from 3 to 6 shoots per crown, where most shoots could be harvested in the same weekly harvest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth period for these plantlet can vary (REINHARDT; CUNHA, 1999;GOMES et al, 2003) for slip-type plantlet, from one to six months, and for shoot-type plantlet, from two to 12 months after the harvest of fruits (REINHARDT; CUNHA, 1999). In addition, it has been elucidated that conventional plantlet are more vigorous and they should have at least 30 cm to be considered suitable for planting (REINHARDT et al, 2018). Additionally, it was observed that the matrices whose shoots were 10 cm in size produced, simultaneously, from 3 to 6 shoots per crown, where most shoots could be harvested in the same weekly harvest.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the above, the challenge is to increase the production of plantlet with superior characteristics to supply the scarcity of propagating material. To this end, several studies have been carried out to improve fast pineapple multiplication methods for the production of plantlet with superior vigor and health such as: micropropagation (OLIVEIRA et al, 2015), stem sectioning (COELHO et al, 2009;FREITAS et al, 2014) and breaking of the apical crown dominance (COELHO et al, 2007a;SANTOS et al, 2014;REINHARDT et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional micropropagation and micropropagation by etiolation of nodal segments are methods that have been previously studied for production of pineapple plantlets. Various protocols have been described in the literature (Kiss, Kiss, Gyulai, & Heszky, 1995;Guerra, Dal Vesco, Pescador, Schuelter, & Nodari, 1999;Barboza & Caldas, 2001;Carvalho et al, 2005;Souza et al, 2010;2012b;Santos, Barbosa, Vieira, & Carvalho, 2015;Reinhardt et al, 2018;Taha, Ibrahim, Gaafar, Zaied, & Shamma, 2019), but no previous study has compared the techniques in vitro, as done in this work.…”
Section: Strategies For Vegetative Propagationmentioning
confidence: 99%
“…The main pineapple cultivar planted in Brazil (Reinhardt et al 2018), known as "Pérola" or "Branco de Pernambuco", has spiny leaf margins and vigorous growth, with long leaves and dark green color. Its fruit has a conical shape, mainly directed to the domestic fresh fruit market.…”
Section: Introductionmentioning
confidence: 99%